Unveiling the Depths of Existential Inquiry: A Qualitative Examination of Psychological Literature (2000-2023) (Global Journal of Human-Social Science, 2023)
Introduction This is a continuation of the previous article Exploring Existential Questions A Comprehensive Review of Psychological Literature 2000-2023 Part 1 the aim of which following on from an analysis that was more quantitative in nature is to present the results of a more in-depth analysis of the articles by means of a qualitative and or mixed approach published between 2000 and 2023 with the aim of understanding how Psychology has appropriated the themes of existential vacuum and meaning of life over this period Method Of the group of articles studied in Part I only articles with qualitative or mixed approaches were analyzed in this second phase in accordance with the following aspects year of publication theoretical references used in the articles concepts employed in the studies context and studied populations emerging themes and relationship between the topic and psychotherapy religiosity and spirituality Results Of the 264 articles selected in Part 1 191 quantitative articles were excluded leaving 73 articles with a qualitative or mixed approach initially classified as follows 46 theoretical qualitative 17 empirical qualitative 7 mixed and 3 interventions
Keywords: existential vacuum; meaning of life; mental health; psychology; qualitative approach; logotherapy